THE EFFECT OF TRADITIONAL GAMES ON THE LANGUAGE DEVELOPMENT - Khasanova Zarnigor Fazliddinovna; Bobokulova Mokhinur Fazliddin qizi (Лучшие интеллектуальные исследования, 2023)
Annotation: This article talks about the effect of Traditional Games on language development of children. Traditional games have become a key tool for integrating young people in our society and gaining self-esteem. Playing traditional games help children to think for themselves, learn cooperation and teamwork skills, work on strategies and tactics, and learn how to hold a conversation with adults. Children play a role in social relations with social behavior, coming from the top of social conflict, social maturation, and self-esteem. The experiences gained while playing games give the child the ability to find solutions to the problems they face in the social environment. Traditional games have been shown to benefit children’s cognitive, emotional, social, and physical development. Hence, it is distressing to see most children miss out on these benefits associated with traditional games. It is determined that traditional games increased the children’s language development in a positive way.